Microsoft security operations analyst exam ref SC-200 certification guide : manage, monitor, and respond to threats using Microsoft Security Stack for securing IT systems /: manage, monitor, and respond to threats using Microsoft Security Stack for securing IT systems. (2022) - Stuart, Trevor; Anich, Joe
No abstract available